Study of fetomaternal outcome in eclampsia - Budhewar, Amita; Ubale, Sunita; Anand, Mamta; Naykodi, Priti; Senapati, Jaynarayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Eclampsia is preventable and treatable cause of maternal mortality and morbidity with poor fetomaternal outcomes in developing countries. Poor knowledge, lack of education, malnutrition and lack of antenatal care major causative factors for increase in eclampsia in developing countries. Methods: This was a retrospective single center observational study including 106 pregnant women with eclampsia in antenatal, intranatal and postnatal period over period of one year in our institute. Results: 106 women included in this study. In present study mean age of the study population was 25.41 years. 1 maternal death reported during study period. Antepartum eclampsia was commonest type 78%. Most of the patients were referred. In this study LSCS most common mode of deliveries. Perinatal mortality rate was 152/1000 live birth. Conclusions: Eclampsia is important cause of maternal and Fetal mortality and morbidity. Prevention of eclampsia is not possible, whereas early diagnosis can be done through clinical signs and symptoms, so as to prevent complications leading to mortality and morbidity related to eclampsia. Improvement in antenatal care services quality, increasing patient awareness about warning symptoms, investigations timely delivery, intensive monitoring in intrapartum and postpartum period have potential to improve fetomaternal outcomes.